Generación con aceites lubricantes usados provenientes de lavadoras y lubricadoras de automotores de las parroquias Santo Domingo de los Colorados, chigüilpe, Río Verde y su incidencia en la contaminación del río Pove en la ciudad de Santo Domingo, provincia de Santo Domingo de los Tsáchilas - Moreno Cusme, Rene Alexander (2015)
This research was conducted between January and July, 2015. The main objective was; to identify the incidence of used lube oil from car wash and lube centers in the parishes; Santo Domingo de los Colorados, Chigüilpe, Río Verde and their impact on Pove´s river pollution. Applied Methods: Field Cards, Statistics diagrams in bars and circles, FODA analysis, water monitoring, flow measurement, Multivariate Analysis, Maps using ArcGis program, and The Improvement Program. Were taken 9 water samples on Pove´s river in 3 sections: High section, medium section, low section, in that sections were analyzed physical – chemical parameters and heavy metals based about the typical composition of used lube oil, stablishing their levels of presence in the river; then the results were compare with the maximum limits on table 10 (Discharge limits to freshwater) Ministerial Agreement 028 which replaced The Libro VI Texto Unificado de Legislación Secundaria del Ministerio del Ambiente: Norma de Calidad Ambiental y de Descarga de Efluentes al Recurso Agua. Acording the statistic applied to physical – chemical parameters and heavy metals, was used the Multivariate Analysis making extractions of redundant factors giving as result that the most discriminant parameters are Zinc and Plumbum. The Flow measurements were making in the same spots that the monitoring water for determination of flowing speed in Pove´s river. The Highest flow was registered at 5th spot in the medium section of Pove´s river (7, 18 m3/s), while the lowest flow was registered at 2nd spot in the high section. The main objective in the Improvement Plan in management was to produce several programs that strengthen prevention measures, to control, to minimize environmental impacts to the water by management of used lubes oils at car wash and lube centers.